Os limites do dano extrapatrimonial reflexo na responsabilidade civil - Domiciano, Bruno Ricarth (2018)
The main objective of this study is to analyze the reflection or ricochet injury as a specific category of injuries in civil responsibility, presenting its legal aspects and also the discussions that may be based on the possibility of being indemnified. At first, will be examined the evolution of civil responsibility, the consequent reprogramming of its function and its repercussions, as well as the legislative discipline granted to the matter by the Brazilian Civil Code of 2002. Then, it will explore the reflection or rebound injury institute, analyzing its concept, the relevant legal dispositions and the species of reflection injuries, focusing on moral injury, the core of these writings. Finally, a more thorough analysis will be made of the applicability of reflection moral injuries by the institute's courts, highlighting the points considered difficult in their arbitration.